"Everybody Knows Everybody": Adolescents' Perceptions of What Helps Them Succeed in a Rural Title I School. Issue 5 (September 2022) - West, Erin M.; Zolkoski, Staci M.; Lockhart, Justin R.; Holm, Jessica M.; Tremont, Josh
The current study explored adolescents' perceptions of what contributes to their experiences of success in a rural Title I school through interpretative phenomenological analysis (IPA). Participants included adolescents who were enrolled at a rural Title I Middle/High School in the southern United States. The single campus school district serves approximately 185 students from Prekindergarten to grade 12. Approximately, 73% of the students are identified as At-Risk, 88% of the students are economically disadvantaged, and 100% of the students qualify for free or reduced lunch. Ten students from this school, with assent and parental consent, participated in the current study. Participants' ages ranged from 13 to 18, and the students represented different genders (seven males, three females) and various racial and ethnic backgrounds (three Black/African American, four Latinx, two White, and one Biracial). Results from the current study suggest low-income adolescents in a rural Title I school perceived (a) school size, (b) family support, and (c) their own internal drive to succeed as contributing to their success at school. These themes, their corresponding subthemes, and representative participant statements are included. Implications for school administrators, teachers, and counselors along with directions for future research are discussed.